Metabolomics - the new "omics" of health care - V.S. Kiranmayi; P.V.L.N. Srinivasa Rao; Aparna R. Bitla (Journal of Clinical and Scientific Research, 2012)
Metabolic diseases are caused by chronic dysregulations of metabolism that differ among individuals due to interactions of the genetic and environmental influences manifesting as a particular phenotype. These are usually diagnosed with the help of individual metabolites which serve as disease biomarkers. However, single biomarker based diagnostics for metabolism-based diseases fails to identify the cause of the alteration of these surrogate markers. This is where metabolomics comes into the clinical picture as it not only helps in assessing the risk of an individual for developing a particular disease but also helps in individualizing therapy based on the metabolic defect. Metabolomics is named in line with other recently developed approaches of diagnostics, i.e., genomics and proteomics. This review provides an overview of the fundamental basic principles, the techniques involved and the applications of this new -omics of healthcare.